2020
DOI: 10.26877/imajiner.v2i5.6520
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Berpikir Kreatif Ditinjau dari Gaya Belajar Siswa Kelas VIII SMP Negeri 1 Sayung Tahun 2019/2020

Abstract: Penelitian ini bertujuan untuk mendeskripsikan kemampuan berpikir kreatif ditinjau dari gaya belajar siswa. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Subjek dalam penelitian ini adalah siswa kelas VIII SMP Negeri 1 Sayung. Teknik analisis datanya terdiri dari empat alur yaitu pengumpulan data, reduksi data, penyajian data, dan verifikasi data. Hasil penelitian ini menunjukkan (1) Siswa bergaya belajar visual mampu menyelesaikan masalah dengan lancar dan dapat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Kemampuan berpikir kritis siswa yang lemah disebabkan salah satunya adalah gaya belajar siswa (Musaidah, Purnomo, and Setyowati, 2020). Hal ini mempersulit tercapainya tujuan pendidikan, salah satunya adalah mengembangkan keterampilan dalam berpikir kritis.…”
Section: Original Articleunclassified
“…Kemampuan berpikir kritis siswa yang lemah disebabkan salah satunya adalah gaya belajar siswa (Musaidah, Purnomo, and Setyowati, 2020). Hal ini mempersulit tercapainya tujuan pendidikan, salah satunya adalah mengembangkan keterampilan dalam berpikir kritis.…”
Section: Original Articleunclassified
“…In this activity, students learn in groups for this because students learn in groups to be able to solve problems by finding various kinds of solutions and answers (fluency), as well as students who use an auditory learning style, are very dependent on hearing captured during the learning process, by listening to what students say they can understand. This can bring up creative ideas owned by students, therefore students can complete with various methods of completion (flexibility) (Musaidah et al, 2020). Based on the results of the study Haslinda et al (2020) about the influence of the use of creative problem solving on creativity can prove, that it is useful for finding and finding new ideas, to produce a work that is useful for problem-solving.…”
Section: Test the Variable Hypothesis Of Creative Thinking Skillsmentioning
confidence: 99%
“…In addition, other studies have been conducted by (Noviyana et al, 2019), who found that learning styles influence student achievement; these results are almost the same as what was done in writing this journal. Then, the re-search by (Musaidah et al, 2020) suggested a link between learning styles and students' mathematical communication abilities. The learning style used is VAK (visual, auditory, and kinesthetic).…”
Section: Introductionmentioning
confidence: 99%
“…The learning style used is VAK (visual, auditory, and kinesthetic). In contrast, the research conducted by the author uses the VARK learning style (graphic, acoustic, read and write, and kinesthetic) (Musaidah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%